In vitro Symbiosis of Reef-Building Coral Cells With Photosynthetic Dinoflagellates - Kawamura, Kaz; Sekida, Satoko; Nishitsuji, Koki; Shoguchi, Eiichi; Hisata, Kanako; Fujiwara, Shigeki; Satoh, Noriyuki (Frontiers in Marine Science, 2021)
Coral reefs are the biodiversity hot spots of the oceans, but they have suffered from increasing environmental stresses caused principally by anthropogenic global warming. The keystone species of coral reefs are scleractinian corals, which maintain obligatory symbiotic relationships with photosynthetic dinoflagellates. Understanding cellular and molecular mechanisms of symbiosis is therefore essential for future preservation of coral reefs. To date, however, almost no in vitro experimental systems have been devised to illuminate such mechanisms. To this end, our previous study established stable in vitro cell culture lines, including IVB5, originating from planula larvae of the scleractinian coral, Acropora tenuis. Here, we show that soon after mixture with the dinoflagellate, Breviolum minutum, flattened amorphous coral cells with endodermal properties exhibited elevated locomotor activity using filopodia and lamellipodia and interacted with dinoflagellates. Several minutes thereafter, coral cells began to incorporate B. minutum, and in vitro symbiosis appeared to have been accomplished within 30 min. Nearly a half of the coral cells had incorporated algal cells within 24 h in a reproducible manner. Coral cells that harbored algal cells gradually became round and less mobile, and the algal cells sometimes settled in vacuole-like structures in coral cell cytoplasm. This symbiosis state was maintained for at least a month. The IVB5 line of A. tenuis therefore provides an experimental system to explore cellular and molecular mechanisms involved in coral-dinoflagellate symbiosis at the single-cell level, results of which may be useful for future preservation of coral reefs.